Mitigating microplastic toxicity: How particle size and degrading bacteria influence Cucumis sativus L. seedlings - Shuyi Chen; Peng Wu; Hao Ren; Guohua Shen; Zhuang Xiong; Wenlin Zhao; Xiang Guo; Peng Xiang; Junqiang Xu; Qiang Li (Ecotoxicology and Environmental Safety, 2025)
Microplastics (MPs) are widely distributed in the environment and have an important impact on the ecosystem. However, there are fewer studies on the effects of microplastics and their degrading bacteria on crops. The aim of this study was to investigate the response mechanism of cucumber seedlings to a 5 ‰ concentration of polystyrene microplastics (PS-MPs) treated with degrading bacteria. Surprisingly, the plant height, stem diameter, and leaf area of cucumber seedlings increased significantly by 17.19 %, 25.54 %, and 15.41 %, respectively, after the application of large PS-MP. The addition of a degrading bacterial mixture improved the agronomic traits of the cucumber seedlings to some extent. The application of small PS-MP and degrading bacteria significantly increased the soil organic carbon content, whereas the large PS-MP had the opposite effect (P < 0.05). Compared to the control group, all treatments significantly increased soil microbial diversity and significantly reduced the abundance of Pseudomonas (P < 0.05). The PS-MPs treatment affected bacterial enzyme functions, including oxidoreductases, while the degrading bacteria enhanced reductase and hydratase functions. Transcriptome analysis further revealed that the PS-MPs treatment affected the biosynthesis process of cucumber seedlings, while treatment with degrading bacteria significantly increased root synthesis and metabolism in the plant. This study enhances understanding of PS-MPs pollution and shows that degrading bacteria, as bioremediation, hold potential for mitigating its adverse effects on plants and soil.